Intersectionality in nursing research: A scoping review - Athena D. F. Sherman; Sarah Febres-Cordero; Kalisha Bonds Johnson; Kristen D. Clark; Meredith Klepper; Brenice Duroseau; Yufen Lin; Wenhui Zhang; Mercy Coleman; Diane Prakash; Gaea A. Daniel; Arzina Tabassum Chand; et al. (Elsevier, 2023)
Background: An intersectional approach to health research provides an analytical foundation to explain the multidimensionality of health status, resource accessibility, privilege, oppression, and current and historical context. The use of intersectionality in health research has known limitations. Its use in health-related fields too often focuses on outcomes, such as health disparities, rather than processes, such as power structures and social determinants. Objective: This scoping review serves to examine how intersectionality has been implemented by nurses in the peer-reviewed literature. We offer insight into how it may be incorporated to inform future nursing research and healthcare provision. Design & Methods: Systematic searches of PubMed (n = 257), SCOPUS (n = 807), EMBASE (n = 396), CINAHL (n = 224), and Health Source: Nursing and Academics (n = 491), published since the seminal publication on intersectionality (1989 - 2023), identified 131 research articles that met inclusion and exclusion criteria. Data extraction and synthesis were used to describe the breadth and depth of the literature specific to the application of intersectionality in nursing research. Results: The included studies used intersectionality to examine the intersections of numerous identities, such as race, gender, and immigration status. However, most studies were descriptive/observational in nature, underreported their methods, and conducted deficit-based research instead of strength-based inquiries. Of note, the vast majority of included articles were published within the last five years. Conclusions: Future researchers using intersectionality as a framework can improve their approach by reporting clear definitions and operationalization of intersectionality. Observational science dominated the included studies; future research should focus on intervention development and evaluation using an intersectional lens. Lastly, caution should be placed on research that focuses solely on deficits among marginalized communities, which places scientists at risk of perpetuating stereotypes or enhancing already-existing stigmas. Tweetable abstract: Scoping review revealed nursing scientists have applied intersectionality in research globally, pointing to its growing role in the advancement of health equity. @emorynursing @athenashermanrn @sfcphdrn